Antimicrobial activities of flavonoid glycosides from Graptophyllum grandulosum and their mechanism of antibacterial action - Cyrille Ngoufack Tagousop; Jean-; Steve Endeguele Ekom; David Ngnokam; Laurence Voutquenne-Nazabadioko (BMC, 2018)
Abstract Background The search for new antimicrobials should take into account drug resistance phenomenon. Medicinal plants are known as sources of potent antimicrobial compounds including flavonoids. The objective of this investigation was to evaluate the antimicrobial activities of flavonoid glycosides from Graptophyllum grandulosum, as well as to determine their mechanism of antibacterial action using lysis, leakage and osmotic stress assays. Methods The plant extracts were prepared by maceration in organic solvents. Column chromatography of the n-butanol extract followed by purification of different fractions led to the isolation of five flavonoid glycosides. The antimicrobial activities of extracts/compounds were evaluated using the broth microdilution method. The bacteriolytic activity was evaluated using the time-kill kinetic method. The effect of extracts on the red blood cells and bacterial cell membrane was determined by spectrophotometric methods. Results Chrysoeriol-7-O-β-D-xyloside (1), luteolin-7-O-β-D-apiofuranosyl-(1 → 2)-β-D-xylopyranoside (2), chrysoeriol-7-O-β-D-apiofuranosyl-(1 → 2)-β-D-xylopyranoside (3), chrysoeriol-7-O-α-L-rhamnopyranosyl-(1 → 6)-β-D-(4"-hydrogeno sulfate) glucopyranoside (4) and isorhamnetin-3-O-α-L-rhamnopyranosyl-(1 → 6)-β-D-glucopyranoside (5) were isolated from G. grandulosum and showed different degrees of antimicrobial activities. Their antibacterial activities against multi-drug-resistant Vibrio cholerae strains were in some cases equal to, or higher than those of ciprofloxacin used as reference antibiotic. The antibacterial activities of flavonoid glycosides and chloramphenicol increased under osmotic stress (5% NaCl) whereas that of vancomycin decreased under this condition. V. cholerae suspension treated with flavonoid glycosides, showed a significant increase in the optical density at 260 nm, suggesting that nucleic acids were lost through a damaged cytoplasmic membrane. A decrease in the optical density of V. cholerae NB2 suspension treated with the isolated compounds was observed, indicating the lysis of bacterial cells. The tested samples were non-toxic to normal cells highlighting their good selectivity index. Conclusions The results of the present study indicate that the purified flavonoids from G. glandulosum possess antimicrobial activities. Their mode of antibacterial activity is due to cell lysis and disruption of the cytoplasmic membrane upon membrane permeability.